I'm new to this subject. I understand the basic laws and that the values of the variables can be either 1 or 0. Here is the formula I have, and the simplification I've done so far.

AB' + A( B' + C' ) + B( B' + C' )

= AB' + A( B' + C' ) + BB' + BC' <-- BB' = 0, removed

= AB' + AB' + AC' + BC' <-- AB' + AB' = AB'

= AB' + AC' + BC' <-- AB' + AC' = A(B' + C' )

= A(B' + C' ) + BC'

I have a feeling I have my groupings wrong. My problem with this so far is I'm not sure which laws to apply when. It all seems pretty haphazard.

Thanks!